A Cross-Sectional Research on Improving Clinical Confidence and Decision-Making Through One Day One Clinical Question (ODOCQ) Program - Masfuri, Masfuri; Liya Arista; Massie, Juliana G.E.P; Andi Amalia Wildani; Puspita Sari, Erna; Hassan, Hamidah (Talenta Publisher, 2025)
Nurses are using knowledge sources to enhance practice through the latest and most trusted evidence-based methods. In this context, the ability to search and select knowledge can increase clinical confidence. Low clinical confidence also leads to hesitation or doubt in decision-making. As an essential element in successfully promoting achievement, the level of confidence and decision-making of the healthcare workforce should be improved. Therefore, this research aimed to determine the frequency of article sharing in improving the level of clinical confidence and decision making after following One Day One Clinical Question (ODOCQ) program. The results showed that ODOCQ was developed for nurses to enhance the capacity of online resources and publications on issues encountered in day-to-day work. A cross-sectional research using random sampling and online questionnaires was also developed to measure clinical confidence and decision-making. Inclusion criteria included one year of minimum service at the hospital, and the research was completed by 118 nurses. In addition, the frequency of article sharing as part of the ODOCQ program improved clinical confidence (p<0.001) and decision-making (p<0.019) significantly. Academic routine habits, such as the ODOCQ program and article sharing frequency, improved clinical confidence and decision-making of nurses, as well as the readiness of evidence-based nursing practice implementation. The program could be used for additional professional development and evidence-based preparation. However, further research is needed to measure the level of clinical confidence and decision-making with non-self-report measurement